Sparsely Wiring Connectivity in the Upper Beta Band Characterizes the Brains of Top Swimming Athletes - Pei, Xinzhen; Qi, Xiaoying; Jiang, Yuzhou; Shen, Xunzhang; Wang, An-Li; Cao, Yang; Zhou, Chenglin; Yu, Yuguo (Frontiers in Psychology, 2021)
Human brains are extremely energy costly in connections and activities. However, it is unknown what is the difference in the brain connectivity between top athletes with long-term professional training and age-matched control subjects, and can balance high-skilled performance and high brain cost. Since elite swimming performance requires athletes to move their arms and legs at different tempos in time with high cooperation skills, we selected an eye-hand-foot complex reaction (CR) task to examine the relations between task performance and brain connection and activities and to explore the energy cost-efficiency of the top athletes. Twenty-one master-level professional swimmers and a control group of 23 age-matched non-swimmer college students were recruited for CR task with concurrent 8-channel EEG recordings. Reaction time and accuracy of the CR task were recorded. Topological network analysis of various frequency bands was performed using the phase lag index (PLI) technique to avoid volume conduction effects. The wiring number of connections and mean frequency were calculated to reflect wiring and activity cost respectively. Analysis showed that professional athletes demonstrate highly skillful arm-leg coordination ability than controls during the performance of the CR task, indexing by faster reaction time and better accuracy than controls. Athlete brain demonstrated significantly less connections and weaker correlations among frontal and parietal regions in upper beta frequency band than controls. However, in low theta frequency band athletes have relatively stronger connectivity between sites of F3 and Cz/C4 sites than controls. Additionally, athletes showed highly stable and low eye-blinking rates across different reaction performance, while controls had high blinking frequency with high variance. Elite athletes’ brain may be characterized with energy efficient sparsely wiring connections in supporting high motor performance and accurate cognitive computation in the hand-foot coordination task.